'Before long there will be nothing but billionaires!' The power of elites over space on the Saint-Tropez peninsula. (19th April 2018) - Bruno, Isabelle; Salle, Grégory
Abstract: Despite its worldwide fame as a fashionable resort and dwelling place of high society, and unlike other elite haunts, the St Tropez peninsula has been overlooked by the social sciences. And yet, it is an emblematic place to observe not only elite self-segregation, but the rise of inequality as well. Based on an ongoing empirical research, this article aims to fill this gap by linking the study of elites to the analysis of social-spatial inequality. It challenges the dominant narrative that simply focuses on elite newcomers charmed by the natural beauty of the area by showing that it took considerable work to adapt local amenities to their tastes. Departing from the common image associated with St Tropez as a show-off place of conspicuous consumption, it also highlights a trend towards 'conspicuous seclusion'. All in all, the case of St Tropez reveals how elites shape their environment through the physical and symbolical power they exert over space.